Selling your business with confidence a practical playbook for mid-market owners - McCombie, David W. (Wiley, 2025)
"Retiring Baby Boomers are creating a Silver Tsunami and over 70% of the 200,000 US mid-market businesses (between USD10 million and USD1 billion in sales) are expected to sell in the coming decade. For most owners, this is the first and only time they will ever sell a business. Because the stakes are so high (the business generally represents 80-90% of their net worth) the sale process becomes an emotional and psychological rollercoaster. Anxiety can significantly be reduced and the odds of a successful outcome improved if they fully understand the process, what to expect, and the implications of the range of options so they can confidently navigate the process"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on October 23, 2024)
Keywords: Sale of business enterprises; Entreprises; Vente